Intelligence in cyberspace: the road to cyber singularity. Issue 4 (4th July 2021) - Priyadarshini, Ishaani; Cotton, Chase
ABSTRACT: Intelligence has been defined in many ways like logic, awareness, reasoning, critical thinking, etc. Many researchers insist on the possibility of a Technological Singularity shortly, which may see machines gaining intelligence similar to, or greater than humans. While many researchers believe that Technological Singularity is at an arm's length, many counter-question the possibility of the same due to the lack of concrete evidence. Recently Cybersecurity has manoeuvred its way through technology to become one of the most rapidly advancing fields. Artificial Intelligence introduced to Cybersecurity has seen a tremendous increase in the number of systems that are capable of performing tasks faster and better than humans. This has led us to believe that there is intelligence in cyberspace along with the possibility of Cyber Singularity. We emphasise the intelligence of systems using a set of characteristics that insist on how sophisticated the systems have become over time that might lead to Cyber Singularity. We map these characteristics to the characteristics of living species with the hope of locating intelligence in the biomedical domain and further, try to identify systems displaying such characteristics in cyberspace. Keeping in mind the concept of technological singularity proposed before, we also perform an extensive survey of the past research works related to the field and also, use the concepts of set theory to reinforce the possibility of Cyber Singularity in the coming years.